2021
DOI: 10.1029/2021ja029238
|View full text |Cite
|
Sign up to set email alerts
|

Wavenumber‐4 Patterns of the Sporadic E Over the Middle‐ and Low‐Latitudes

Abstract: The COSMIC radio occultation observations are used to investigate the wavenumber‐4 (WN4) structure of the Sporadic E (Es) layer during 2007–2018. The WN4 pattern is observed in the Es occurrence rate over the middle‐ and low‐latitudes. This pattern is stronger at the low‐latitudes than at the middle‐latitudes. It shows the peak intensity in latitude bands between 5° and 15° dip latitudes in both hemispheres. The WN4 structure occurs predominantly during daytime. It appears above 110 km in the morning, then des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Herein, the wave‐4 structure of the diurnal tidal amplitudes can further explain the results of Liu et al. (2021) and Niu (2021). Note that compared with other seasons, the amplitude of the DE3 in winter is the smallest, which could explain that the diurnal tide does not present the wave‐4 structure in winter.…”
Section: Discussion and Summarysupporting
confidence: 71%
See 1 more Smart Citation
“…Herein, the wave‐4 structure of the diurnal tidal amplitudes can further explain the results of Liu et al. (2021) and Niu (2021). Note that compared with other seasons, the amplitude of the DE3 in winter is the smallest, which could explain that the diurnal tide does not present the wave‐4 structure in winter.…”
Section: Discussion and Summarysupporting
confidence: 71%
“…Recent researcher (e.g., Liu et al, 2021;Niu, 2021) found the wavenumber 4 pattern in Es layer intensity and Es layer occurrence rate at low latitudes. Herein, the wave-4 structure of the diurnal tidal amplitudes can further explain the results of Liu et al (2021) and Niu (2021). Note that compared with other seasons, the amplitude of the DE3 in winter is the smallest, which could explain that the diurnal tide does not present the wave-4 structure in winter.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Furthermore, the longitudinal wavenumber‐4 (WN4) structure is observed in the occurrence and intensity of E s layers at low latitudes and midlatitudes (Z. Liu, Fang, et al., 2021; Z. Liu, Li, et al., 2021; Niu, 2021b; Niu et al., 2019). The occurrence of the WN4 structures strongly depends on the season.…”
Section: Model Variablesmentioning
confidence: 99%
“…Terdiurnal and querterdiurnal tidal signatures in Es occurrence rate are also indicated in other publications (e.g., Haldoupis & Pancheva, 2006;Fytterer et al, 2013;Jacobi et al, 2019). Recently, Liu et al (2021) revealed a wavenumber 4 pattern in Es occurrence rate at mid and low latitudes formed by eastward propagating non-migrating diurnal tide with zonal wavenumber 3, and a similar feature was detected in the vertical shear of the zonal wind. Shinagawa et al (2017) calculated the vertical ion convergence rate using GAIA (Ground-to-topside model of Atmosphere and Ionosphere for Aeronomy) simulations to show how the geographical and seasonal variations of wind shears are consistent with those in EsOR.…”
Section: Introductionmentioning
confidence: 63%